2016
DOI: 10.1007/s10461-016-1609-1
|View full text |Cite
|
Sign up to set email alerts
|

Misreporting of Product Adherence in the MTN-003/VOICE Trial for HIV Prevention in Africa: Participants’ Explanations for Dishonesty

Abstract: Consistent over-reporting of product use limits researchers’ ability to accurately measure adherence and estimate product efficacy in HIV prevention trials. While lying is a universal characteristic of the human condition, growing evidence of a stark discrepancy between self-reported product use and biologic or pharmacokinetic evidence demands examination of the reasons research participants frequently misrepresent product use in order to mitigate this challenge in future research. This study (VOICE-D) was an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 19 publications
2
46
0
Order By: Relevance
“…While some of this difference could be related to dilutional effects of pregnancy (potentially both increased plasma volume and increased vaginal secretions), the PK parameters on Day 0, 8 h after observed dosing, were observed to be similar between this pregnant cohort and nonpregnant comparators [11]. The challenges of suboptimal adherence and accurate product use reporting in HIV prevention method research have been well documented in other recent microbicide studies [1215]. In the VOICE trial, as with other microbicide studies, a variety of social and contextual factors influenced women’s ability and willingness to consistently use products on a daily basis [16].…”
Section: Discussionmentioning
confidence: 84%
“…While some of this difference could be related to dilutional effects of pregnancy (potentially both increased plasma volume and increased vaginal secretions), the PK parameters on Day 0, 8 h after observed dosing, were observed to be similar between this pregnant cohort and nonpregnant comparators [11]. The challenges of suboptimal adherence and accurate product use reporting in HIV prevention method research have been well documented in other recent microbicide studies [1215]. In the VOICE trial, as with other microbicide studies, a variety of social and contextual factors influenced women’s ability and willingness to consistently use products on a daily basis [16].…”
Section: Discussionmentioning
confidence: 84%
“…Patients in other prevention studies have also reported good adherence despite objective evidence to the contrary (29, 30). Finally, although the local institutional review boards approved reimbursement for study-related expenses as appropriate, this could have influenced patients to report good adherence (31). …”
Section: Discussionmentioning
confidence: 99%
“…Of importance in this study was that only 1% of participants were concerned about providing a sample that could reveal their adherence level and other studies have suggested that provision of drug levels could improve subsequent drug-taking. [35, 36] However, both DBS and hair require expensive liquid chromatography/ tandem mass spectrometry equipment for analyses and are performed in high-level research laboratories in the U.S. Lower-cost methods that can be applied to real-world implementation in the field and to assess drug taking using point-of-care technology will be the next advances in the field.…”
Section: Discussionmentioning
confidence: 99%